Fuzzy Technique used for Energy Loss Determination in Medium and - Bobric, E. C.; Cartina, G.; Grigoras, G. (Elektronika ir Elektrotechnika, 2009)
Energy losses levels represent an interesting indicator in planning and operation activities of distribution system. This indicator depends by a number of parameters and variables, such as: nominal voltage, transformer capacity, number of substation, electric line parameters, loads level, etc. For energy losses minimization are necessary both development planning, modernization of distribution networks and utilization of management and exploitation techniques, based on intelligent equipment, performance software techniques, which facilitating the realizing of this objective. In this paper is presented the applications of fuzzy techniques for load estimations and determination of energy loss in distribution network. Numerical results make obvious in that presented method is rather precise, robust and simple of applied. Ill. 4, bibl. 7 (in English; summaries in English, Russian and Lithuanian).